Exploring Emotions and Bilingual Identity with Adults from Turkiye Living in Ireland through Arts-based Research - Boynuegri, Ebru (Trinity College Dublin. School of Education. Discipline of Education, 2026)
This Arts-based Research explores the emotions and bilingual identity of 22 participants, 21 adults from Turkiye living in Ireland who attended a bilingual storytelling performance based on The Epic of Gilgamesh, and the performing artist. The performance, titled The Fertile Crescent: Tales from the Orient, was held on four separate occasions, each followed by a post-performance workshop facilitated by the researcher. The research asked the overarching question "How do individuals who are speakers of English as a second language construct their identities across linguistic, personal, social and cultural dimensions?", explored through three sub-questions. Data was interpreted using creative data analysis, yielding seven themes. The first three themes focus on emotions: (1) Barefoot in the biting, yet reviving waters, (2) Finding home in the world of the known, and (3) Finding home in the universe of the felt. They address, respectively, (1) emotions as responses to English, (2) emotions as responses to Turkish, and (3) emotions as responses to a requiem sung in the play. The fourth and fifth theme focus on bilingual identity: (4) Fractured selves in English speech and (5) Bilingual voices under pressure. These themes address, respectively, (4) oral fluency and accent anxiety, and (5) translanguaging anxiety. Within the latter, I advance the concept of Plaza Turkish Anxiety. The sixth theme, (6) Selves in connection, trust, pride, gender and existence, focuses on sociocultural and personal selves. The seventh theme, (7) Lotus of the atom, atom of the lotus, considers Professional Artist Identity within sociocultural, personal and bilingual selves. To address the overarching question, these themes were knitted into six threads: language and emotion; language and identity; possible selves as a bilingual speaker; Professional Artist Identity; unlocking the chain ball: from language anxiety to creative empowerment; and identity exploration through Arts-based Research. The findings are further represented through three poems, one per sub-question. The artistic layers of this study are also enriched by its structure, which mirrors The Epic of Gilgamesh - a poetic work rich in metaphor. Some concepts are encapsulated through metaphors, such as bilingualism compared to Humbaba, a character from the epic, the awe-inspiring guardian of the Cedar Forest, a figure whose presence inspires both fear and wonder, anxiety and empowerment. The study also suggests that fear and anxiety related to bilingualism can be reimagined by the perceived creative use of language.
APPROVED
Keywords: Bilingual Identity; Professional Artist Identity; Emotions; Translanguaging; Plaza Turkish Anxiety; Arts-based Research; Research-based Theatre; Poetic Inquiry